Characterization and performance of Schottky diode based on wide band gap semiconductor ZnO using a low-cost and simplified sol-gel spin coating technique - Farag, A. A. M.; Farooq, W. A.; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2011)
In this study, a Schottky diode based on wide band gap semiconductor ZnO was fabricated on p-type Si substrate using sol-gel spin coating method. Al/ZnO/p-Si diode indicates a rectification behavior. At lower voltages, the forward current of the diode was found to obey the intrinsic thermally generated charge carriers and at relatively higher voltages, the current mechanism of the diode is controlled by a space charge limited conduction mechanism. Under reverse bias conditions, the current-voltage characteristics of the diode exhibit the lower current as compared under forward bias, indicating the existence of a current limitation mechanism induced by two field lowering mechanisms which are Poole-Frenkel and Schottky mechanisms. The parameters, series resistance R(S), the ideality factor n and the barrier height phi(B0) of the diode were determined by performing different plots obtained from the experimental forward bias current-voltage. The capacitance measurements show that the values of capacitance were almost independent of the forward bias under various frequencies. The higher values of the capacitance at low frequencies were attributed to the excess capacitance resulting from the interface states in equilibrium with the ZnO. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Schottky contact; n-ZnO; Barrier height; Series resistance